PENINGKATAN PROFESIONALISME GURU SEBAGAI KUNCI MENINGKATKAN KUALITAS PENGAJARAN DAN PENDIDIKAN - Sulfiani, Besse; Cipta Pramudita, Andi; Alfionita; Angri Nanda, Dwi; Karmila, Lilis; Asmidin, Andi; Arief Rosyidin, Muh. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Quality education forms the primary foundation for shaping a competent and competitive generation. Teachers, as the spearhead of the learning process, play a strategic role in creating a learning environment that is effective, engaging, and responsive to contemporary needs. This study aims to analyze the impact of enhancing teacher professionalism on teaching methods and its implications for achieving quality education. A descriptive qualitative approach was employed, utilizing interviews, classroom observations, and documentation studies. The findings reveal that continuous professional development, competency enhancement, and reflective learning practices significantly contribute to teaching innovation, improved teacher-student interaction, and more optimal learning outcomes.